Sovereign : the Books of Mortals - Dekker, Ted, 1962- (Dekker, Ted, 1962- Books of mortals, 2013)
Nine years after Rom Sebastian was thrust into the most unlikely of circumstances as hero and bearer of an unimaginable secret, the alliance of his followers is in disarray. An epic battle with The Order has left them scattered and deeply divided both in strategy and resolve in their struggle to become truly alive and free. Only 49 truly alive followers remain loyal to Rom. This meager band must fight for survival as The Order is focused on their total annihilation. Misunderstood and dispised, their journey will be one of desperation against a new, more intensely evil Order. As the hand of this evil is raised to strike and destroy them they must rely on their faith in the abiding power of love to overcome all and lead them to sovereigncy.